Flow and performance analysis of H-Darrieus hydroturbine in a confined flow: A computational and experimental study. (October 2016) - Gorle, J.M.R.; Chatellier, L.; Pons, F.; Ba, M.
Abstract: Increasing demand for renewable energy due to the limitations in using the hydrocarbon fuels and their availability is a debating topic. To this end, wind and tidal energy sources are grabbing the attention in both academics and industry. However, better exploitation of such renewable systems require a detailed information about the flow physics due to the unsteady effects and non-linearities of the flow. This paper presents the performance and flow evaluation for a low-speed hydrokinetic turbine of Darrieus type, operating in a confined flow channel. The investigation methods include computations (2D CFD) using Chimera meshes and experiments (2D-2C PIV) including phase-locked measurements. SST k − ω turbulence model based numerical results for velocity fields, instantaneous vortex dynamics, wake geometry and Q -criterion are validated using experimental findings. Continuous validation of performance measurements takes blockage effects into account. This is important due to the neglected 3D flow variations in computations. Also, the influence of incoming stream velocity on turbine's performance and flow pattern is analysed. Such an inclusive analysis helps to qualify the turbine design as well as investigation methods for practical applications with a focus on flow confinement.